Analysis of Students Difficulties in Completing The Service Company Accounting Cycle Learning in Class X and XI AKL Students of SMK Muhammadiyah 2 Karanganyar - Putri, Vernanda Wigia; Budiyanto, Sapta Mei (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this study was to describe the learning difficulties of class X and XI akl students in completing service company accounting learning at smk muhammadiyah 2 karanganyar, as well as to describe the impact of accounting learning difficulties and describe the efforts made to reduce students' learning difficulties. The method in this study uses qualitative research. The research design used is ethnography. The data collection techniques used in this research are interviews, observation and documentation. The data sources used in this study were subject teachers and students in grades X and XI. Data analysis techniques use data reduction, data presentation and conclusion making. Data validity techniques in this study used triangulation, researchers used 3 types of triangulation, namely source triangulation, method triangulation and time triangulation. The results showed that there were several difficulties experienced by students in completing the accounting cycle learning, namely difficulties in analysing journal transactions and difficulties when calculating journal transactions. From some of these difficulties, the impact that occurs is that students get unsatisfactory grades either on tests or doing assignments. However, from the impact that occurs, there is a solution that is used as a way out to reduce this learning difficulty, according to the teacher, the solution that will be done is to evaluate students such as conducting daily tests, asking again about material that has not been fully understood by students and explaining it again. As for the solutions that will be carried out by students to reduce these learning difficulties are to study the material provided again, ask the teacher for material that has not been understood, and do group study.